Industrial Revolution 4.0 (IR 4.0) competencies: a literature review of manufacturing industry - Hussain Matar Mohamed Ghaith Alhosani; Ahamat, Amiruddin; Ismail, Norain (Allied Business Academies, 2021)
Manufacturing industries are different from what they were a decade ago due to challenges related to IR 4.0. The main challenges are associated with the lack of leadership, knowledge, and talent workers; all are linked to the competencies needed for the workers in the Era of IR4.0 manufacturing industry. Therefore, this study investigates the landscape of the required competencies by exploring the previously published articles. This study is based on an illustration of a literature review to provide a comprehensive IR4.0 competency model for manufacturing industries. The proposed model illustrates a total of 64 skills and competencies, which can be classified into twenty classes on the second level. A higher level can classify it into eight classes based on the SHL competency classification approach. The results indicate that many behavioral competencies should be conformed through all workers, such as decision making. It implies that workers of the future ought to successfully carry a higher level of behavioral competencies to work in Industry 4.0. Only competencies under the dimension "Applying Expertise and Technology" have three variants of advanced technology-based components. These variations are allocated into three categories; information system, computer science, and engineering focusing on manufacturing industries. Thus, competencies such as interdisciplinary working, collaboration, interaction, or teamwork will have a distinctive function.